2020
DOI: 10.1371/journal.pone.0233148
|View full text |Cite|
|
Sign up to set email alerts
|

Using mechanical testing to assess texturing of prosthetic sockets to improve suspension in the transverse plane and reduce rotation

Abstract: Creating a secure and comfortable linkage between the residual limb and prosthetic socket in persons with lower limb amputation is a critical factor for successful rehabilitation, including ambulation and other activities of daily living. Unwanted rotation within the socket can be a clinical problem for prosthesis users. One way of addressing issues experienced with transverse plane control of the socket may be through increased friction interface forces. It has been proposed that friction at the residual limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Various suspension methods, including suction, vacuum-assisted, and strap-based systems, are utilized to achieve secure and comfortable suspension. The socket design should accommodate the necessary suspension mechanism while ensuring stability and minimizing unwanted movements (Quinlan et al, 2020a(Quinlan et al, , 2020b.…”
Section: Socket Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Various suspension methods, including suction, vacuum-assisted, and strap-based systems, are utilized to achieve secure and comfortable suspension. The socket design should accommodate the necessary suspension mechanism while ensuring stability and minimizing unwanted movements (Quinlan et al, 2020a(Quinlan et al, , 2020b.…”
Section: Socket Designmentioning
confidence: 99%
“…This adaptability extends the lifespan of the socket and ensures an optimal fit and function over time. The interface between the residual limb and the socket, along with the suspension system, significantly influences socket performance (Quinlan et al, 2020a). Soft interfaces, such as silicone liners, help improve comfort, cushioning, and moisture management.…”
Section: Socket Designmentioning
confidence: 99%
“…Surface roughness helps the patient by controlling the unnecessary rotation of a socket. 11 In 2020, Quinlan et al 12 using recently created testing procedures, revealed that various textured patterns greatly enhanced torque in the transverse plane more than smooth sockets, particularly for passive suction.…”
Section: Introductionmentioning
confidence: 99%